KINETIC ANALYSIS OF IMINE AND HYDRAZONE HYDROLYSIS IN A PHYSIOLOGICALLY RELEVANT CONTEXT - Al-Mansoori, Ahmed Ali; Al-Hussein, Layla Amira; Al-Abdullah, Karim Saad (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
The addition of nucleophilic species to carbonyl groups, leading to the formation of tetrahedral intermediates that subsequently undergo an addition-elimination mechanism, is a fundamental chemical process. Such reactions are particularly significant in the context of primary amino groups and aldehydes, as they serve as model reactions for various biological processes. This study delves into the kinetic aspects of the hydrolysis of imines, which are intermediates formed during these reactions, with a focus on their behavior in aqueous acidic environments. The hydrolysis of imines, especially those derived from primary amino groups and aldehydes, is a complex process with several potential reaction pathways. To gain insights into the kinetics and mechanisms governing these reactions, we examined the work of Hine et al. [1] and Cords and Jencks [2], who have contributed valuable insights in this area. Their research laid the foundation for our investigation. In this study, we present a comprehensive analysis of the kinetics of imine hydrolysis in aqueous acid. We aim to elucidate the factors influencing the rate of this reaction and its mechanistic details. By employing kinetic methods, we have gathered data that sheds light on the reaction intermediates and the overall reaction mechanism. Our findings offer a deeper understanding of the behavior of primary amino group-containing compounds when reacting with aldehydes, particularly in acidic conditions, which have relevance in both synthetic and biological contexts.